2020
DOI: 10.1186/s12879-020-05248-4
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care thrombocyte function testing using multiple-electrode aggregometry in dengue patients: an explorative study

Abstract: Background Dengue virus (DENV) causes the hospitalisation of an estimated 500,000 people every year. Outbreaks can severely stress healthcare systems, especially in rural settings. It is difficult to discriminate patients who need to be hospitalized from those that do not. Earlier work identified thrombocyte count and subsequent function as a promising prognostic marker of DENV severity. Herein, we investigated the potential of quantitative thrombocyte function tests in those admitted in the very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Activated platelets undergo degranulation, attach themselves to the vascular wall and form thrombi, effectively removing them from the circulation, which results in thrombocytopenia. Despite this activation, platelets from dengue patients are hyporesponsive to procoagulant stimuli in aggregometry assays, which is likely the result of exhaustion [ 65 ]. This illustrates thrombocytopenia and platelet dysfunction go hand in hand during DENV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Activated platelets undergo degranulation, attach themselves to the vascular wall and form thrombi, effectively removing them from the circulation, which results in thrombocytopenia. Despite this activation, platelets from dengue patients are hyporesponsive to procoagulant stimuli in aggregometry assays, which is likely the result of exhaustion [ 65 ]. This illustrates thrombocytopenia and platelet dysfunction go hand in hand during DENV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Further clinical correlation demonstrated that lower AUC may indicate the severity of the disease and may correlate with the duration of the hospital stay. 17 In the context of other viral hemorrhagic fevers such as Crimean‐Congo hemorrhagic fever, Lassa fever, and Argentinian hemorrhagic fever, platelet aggregometry studies have suggested that the coagulopathy is clearly due to defects in platelet function and aggregation. 18 , 19 The findings of the study on Crimean‐ Congo hemorrhagic fever found that mucosal bleeding was not due to thrombocytopenia but rather due to platelet dysfunction in aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the investigators of the above study did not find any correlation between platelet count and platelet aggregation/AUC. Further clinical correlation demonstrated that lower AUC may indicate the severity of the disease and may correlate with the duration of the hospital stay 17 . In the context of other viral hemorrhagic fevers such as Crimean‐Congo hemorrhagic fever, Lassa fever, and Argentinian hemorrhagic fever, platelet aggregometry studies have suggested that the coagulopathy is clearly due to defects in platelet function and aggregation 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In this matter, POCT devices detecting platelet aggregation has been developed. Multiplate™ multiple-electrode biosensor potential was evaluated for platelet aggregation ( De Jong et al, 2020 ). Platelets become adhesive upon activation with reagents and got deposited onto the metal sensor wires that led to increase in electrical resistance.…”
Section: Iomt-assisted Poc Biosensing For Infectious Diseasesmentioning
confidence: 99%